PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN AKUNTANSI SUMBER DAYA MANUSIA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - AGUS PURNOMO, MUHAMMAD; , HARIYATI (Jurnal Akuntansi AKUNESA, 2018)
This study aims to determine the effect of company size, profitability, company age on disclosure of human resource accounting. The research sample is all banking companies on the Indonesia Stock Exchange (IDX). The sample obtained was 43 companies. The data collection technique used is documentation. This study uses multiple regression analysis using statistical package for social sciene (SPSS.22) software. The results showed that the size of the company in this study had a positive effect on disclosure of human resource accounting. However, the profitability and age of the company does not affect the disclosure of human resource accounting.Keywords : Company Size, Profitability, Company Age, Human Resource Accounting Disclosure